Suspicion ebook - Finder, Joseph (2014)
One bad choice gets a father caught up in a deadly situation in this electrifying thriller from New York Times bestselling author Joseph Finder. Single father Danny Goodman suddenly finds himself unable to afford the private school his daughter adores. Then Danny meets Thomas Galvin, the father of his daughter's new best friend and one of the wealthiest men in Boston. Out of the blue Galvin offers a loan to help Danny out. Desperate, he takes the money, promising to pay it back. But the moment the money is wired into his account, the DEA comes knocking. Danny’s impossible choice: an indictment for accepting drug money, or a treacherous assignment to help the government get close to his new best friend. As Danny begins to lie to everyone in his life, including those he loves most, he must decide once and for all who the real enemy is or risk losing everything—and everyone—that matters to him.